2008
DOI: 10.1108/02635570810868380
|View full text |Cite
|
Sign up to set email alerts
|

The effects of team reflexivity and innovativeness on new product development performance

Abstract: Purpose-To determine the effects of project management skills, entrepreneurial proclivity, and existing knowledge on team reflexivity and performance of cross-functional new product development (NPD) team. The moderating roles of team cohesiveness and knowledge practice are also explored. Design/methodology/approach-This study used online questionnaire surveys by inviting 500 R&D team members of NPD from three Science Parks in Taiwan. The survey questionnaires were sent to the representative of R&D team member… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 72 publications
1
7
0
3
Order By: Relevance
“…These include, for example, individual skills and capabilities, collective culture and structural aspects. There are some examples in the current literature suggesting that team reflection is a driver of both team innovation (Somech, 2006) and product innovation (Tien-Shang Lee, 2008). According to Somech (2006), the process of team reflection serves as a vehicle through which the interaction of participative leadership style and functional heterogeneity enhances team innovation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These include, for example, individual skills and capabilities, collective culture and structural aspects. There are some examples in the current literature suggesting that team reflection is a driver of both team innovation (Somech, 2006) and product innovation (Tien-Shang Lee, 2008). According to Somech (2006), the process of team reflection serves as a vehicle through which the interaction of participative leadership style and functional heterogeneity enhances team innovation.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Cascio (2011) and Atalaya et al (2013) have proven that innovation marketing is not an important driver for improving MP. In addition, some dimensions of innovative marketing such as product innovativeness are truly decisive for improving business performance in both MP and financial performance (Lee, 2008;Lages et al, 2009;Ar, 2012), but some studies are not in line with these findings. Yalcinkaya et al (2007) showed clearly that innovation products have no effect on MP.…”
Section: Introductionmentioning
confidence: 97%
“…(2009) find that profitability performance and growth performance in small and medium enterprises are determined by product innovation. Research in Asian countries conducted by Rosli and Sidek (2013) in Malaysia and Lee (2008) in Taiwan also shows that product innovation really becomes decisive factor for improving corporate performance.…”
Section: Innovativeness (Inn) and Marketing Performance (Mrp)mentioning
confidence: 98%